Effects of Duration of Diabetes and Diabetes Therapy (Metformin) on Fbxw7 Levels in Iraqi Type II Diabetic Patients (Medico Legal Update, 2021)
Background: This study concentrated on evaluation the FBXW7 levels and other markers in T2DM patients related to the duration of metformin monotherapy and duration of T2DM. Method: The current study includes 60 diabetic patients type II and30 control subjects. The groups of patients were subdivided in to two groups: (group I) (30) Newly diagnosed T2DM which also subdivided to two groups(> 1 year, and 1 year and